Сфера сенсів у динаміці розвитку суспільства в контексті змін семіотичної реальності культури - Грушко, Віктор Сергійович; Grushko, Viktor S. (Східноєвропейський національний університет імені Лесі Українки, 2017)
Українське суспільство тривалий час перебуває в стані болісного розпаду радянської семіотичної реальності й становлення нової. Утрата старих сенсів не привела до автоматичного їх заміщення новими, а натомість породила смислову дезорієнтацію в українському соціумі, унаслідок чого в країні запанували відцентрові сили, атомізація суспільства, у якому особистий інтерес, не облагороджений високим сенсом, перетворився в руйнівну силу. У роботі розкрито провідну роль соціокультурних сенсів у життєдіяльності людських спільнот, становленні семіотичних реальностей та їх внесок у формування соцієтальних систем. Проаналізовано специфіку взаємодії між собою різних сенсів і керованих ними соціумів, виявлено існування ієрархії між ними; обґрунтовано причини світоглядних криз у ході розвитку соціумів і визначено роль, яку відіграють періоди смислової дезорієнтації під час трансформації людських спільнот у нову якість. Every society is periodically undergoing ideological breaks when the old meanings lose their appeal to the majority, resulting it erodes the appointed social ties and decays social institutions. Ukrainian society is undergoing such difficult period nowadays, when it loses heart the ideals and values of the Soviet era and painfully looking for a new meaning in the post-colonial reality. Reasonable key role in the senses filled with the lives of individuals and human communities to certain content and their impact on the determination of their tactical and strategic goals in life, combined with the methods for achieving them. The mechanism senses influence on the formation of complex societies to build societal systems, the dynamics of the formation and destruction of human civilizations. The analysis of interaction between the different meanings that can engage each other in various qualities relationship of conflict to symbiotic, from attempts to take only a single well-defined niche in society attempts to cover almost all aspects of society, from constructing an ordered hierarchy of relations between the state of the lack of a unified system of priorities. The role of ideological and semantic crises that accompanied the collapse of the social system in which people comprehend in a new reality, form new meanings that are able to combine them for future joint actions and achieve new and important goals.
Area of Meanings in the Dynamics of Society Development in the Context of Semiotic Reality Culture
Keywords: соціокультурні сенси; точка біфуркації; соцієтальні системи; ієрархія смислів; смислова дезорієнтація; socio-cultural meanings; semiotic reality; bifurcation point; societal system; hierarchy of meanings